Wayfinding difficulties among elders with dementia in an assisted living residence. (July 2014) - Caspi, Eilon
The concerning phenomena of spatial disorientation and wayfinding difficulties among elders with Alzheimer's disease or a related dementia in assisted living residences are understudied. This qualitative study aimed to identify the types of wayfinding difficulties as experienced by residents with memory-loss in two special care units of an assisted living residence. The data collection period included participant observation complemented by semi-structured interviews with care staff and managers and review of clinical records. A wide spectrum of wayfinding difficulties was identified as experienced by six residents. The residents experienced difficulties reaching several destinations on the units. The implications of the findings to practice, architectural design, and policy are discussed.